Immunogenicity, safety and reactogenicity of a Phase II trial of Vi-DT typhoid conjugate vaccine in healthy Filipino infants and toddlers: A preliminary report. Issue 28 (9th June 2020) - Capeding, Maria Rosario; Alberto, Edison; Sil, Arijit; Saluja, Tarun; Teshome, Samuel; Kim, Deok Ryun; Park, Ju Yeon; Yang, Jae Seung; Chinaworapong, Suchada; Park, Jiwook; Jo, Sue-Kyoung; Chon, Yun; et al.
Highlights: Vi-DT is safe and well tolerated in infants and toddlers aged 6–23 months. Vi-DT showed >1000-fold higher Geometric Mean Titer (GMT) compared to Placebo. 100% seroconversion reported in Vi-DT group in all age strata. Abstract: Background: Typhoid fever remains an important public health problem in developing countries and is endemic in many parts of Asia and Africa where the incidence of disease typically peaks in school-aged children. Age restrictions and other limitations of existing oral live-attenuated typhoid and parenteral Vi polysaccharide vaccines have triggered the development of Vi conjugate vaccines with improved immunological properties, use in younger age range, and longer durability of protection. We present the safety, reactogenicity, and immunogenicity data from a Phase II study after a single dose of Vi polysaccharide conjugated to diphtheria toxoid (Vi-DT) conducted in 6–23-month old Filipino children. Methods: This is a randomized, observer-blinded Phase II study to assess the immunogenicity, safety and reactogenicity of Vi-DT compared to placebo, conducted in Muntinlupa City, The Philippines. Participants aged 6–23 months were enrolled and randomized to Vi-DT (25 µg) or placebo (0.9% sodium chloride) and evaluated for immunogenicity and overall safety 28 days post vaccination. Results: A total of 285 participants were enrolled and age-stratified: 6 to < 9 months, 9–12 months, and 13–23 months. Seventy-six (76) participants received Vi-DT and 19 received placebo per each strata. All participants seroconverted after a single dose of Vi-DT versus 7% of placebo recipients. Anti-Vi IgG GMT was 444.38 [95% CI (400.28; 493.34)] after a single dose of Vi-DT; there was no change in GMT after placebo administration, 0.41 [95% CI (0.33; 0.51), p < 0.0001]. A similar pattern of immunogenicity was reported across all age strata. The vaccine reported to be safe and well tolerated. Conclusions: Vi-DT vaccine was immunogenic, safe, and well tolerated in children aged 6–23 months. ClinicalTrials.gov registration number: NCT03527355.